Public Investment and Fiscal Policy : Lessons From the Pilot Country Studies. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper reports on findings from eight pilot country studies on public investment that were carried out during the second half of 2004. The pilot country studies covered a diverse group of countries. Specifically, they included countries in Latin America (Brazil, Chile, Colombia, and Peru), Africa (Ethiopia and Ghana), the Middle East (Jordan), and Asia (India).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet